Medical Disorders of Pregnancy among Inpatients at a Tertiary Level Hospital - Baral, Gehanath; Joshi, Rijuta; Subba, Preksha; Pokhrel, Shreeshiya; KC, Sunita; Baree, Zahiya A (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim of the study was to determine the pattern of medical disorders in admitted pregnant women. Methods: A descriptive retrospective study was conducted for a year at Paropakar Maternity and Women’s Hospital in Kathmandu in 2016. Results: In a year of 2016, 2.4% of 20521 pregnant women admitted had medical disorder with 87% at optimal age of reproduction (20-35 years). The commonest disorders were hypertensive disease of pregnancy (68%), urinary tract infection (11%), other infectious conditions (5%), thyroid disorder (5%), diabetic complications (2%) and cardiac disease (0.4%). Conclusions: Hypertensive disorder is predominant medical disorder of pregnancy followed by urinary tract infection, endocrine disorder and viral infections in order.